Determinants of work alienation among bank employees: a socioeconomic perspective - Sabia Singh; Gurpreet Randhawa (Vilakshan (XIMB Journal of Management))
Purpose – This study aims to identify various socioeconomic variables that influence the development of work alienation among Indian bank employees. Design/methodology/approach – Data were collected from a sample of 552 employees working in ten public and ten private sector banks in Punjab. Statistical techniques such as the independent sample t-test, Welch’s F-test, and Games–Howell procedure were used for data analysis. Findings – Results of this study indicated that socioeconomic variables, namely, age, educational qualification, monthly income, and work experience, significantly influence work alienation among bank employees. In contrast, gender, marital status, type of bank, and cadre did not have any significant relationship with work alienation. Originality/value – This study is one of the limited research studies that has examined the linkage between socioeconomic variables and work alienation in the context of the banking sector of a developing nation like India.